Synthesis, Characterization, Nonlinear Absorption and Electrochromic Properties of Double-Decker Octakis(mercaptopropylisobutyl-POSS)-phthalocyaninatolanthanide(III) Complexes - ÖZKAYA, ALİ RIZA (WILEY-V C H VERLAG GMBH, 2008)
In this study, the sandwich-like bis(phthalocyaninato)lanthanide(III) Complexes MPC2 (M = Lu, Gd) have been prepared, The reaction of 4,5-bis(mercaptopropylisobutyl-POSS)-phthalonitrile (1) [POSS: polyhedral oligomeric silsesquioxane] with lithium gave the dilithium octakis(mercaptopropy)-isobutyl-POSS)phthalocyaninate which was further reacted in situ with Lu(OAc)(3)center dot 3H(2)O and Gd(OAc)(3)center dot 4H(2)O in 1-pentanol to give compounds 2 and 3, respectively, The structure of the target compounds was confirmed by elemental analysis, UV/Vis and IR spectroscopic as well as MALDI-TOF mass spectrometric techniques. The nonlinear absorption and optical limiting (OL) performance of 2 and 3 are investigated by means of the Z-scan technique. While 2 exhibits a good nonlinear absorption, 3 possesses a low nonlinear absorption. The ratio of the excited-state to ground-state absorption cross sections, k, the effective nonlinear absorption coefficient, beta(ett), and the energy density, F-sat, were determined for 2. The results indicated that 2 possesses a good combination of optical limiting parameters. (C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Phthalocyanines; Lanthanides; Nonlinear optics; Optical limiting; Electrochromism; GAS-SENSING PROPERTIES; SANDWICH-TYPE (NA)PHTHALOCYANINATO; OPTICAL LIMITING PROPERTY; ELECTROCHEMICAL PROPERTIES; SPECTROSCOPIC CHARACTERIZATION; REDOX PROPERTIES; METAL-COMPLEXES; PHTHALOCYANINE; NAPHTHALOCYANINE; CONDUCTIVITY